ANALISIS DAMPAK DAN KONSEKUENSI PENGGUNAAN MEDIA SOSIAL TERHADAP TINGKAT BUNUH DIRI PADA USIA DEWASA AWAL: A SYSTEMATIC LITERATURE REVIEW - Salsabila, Salma Nehaya; Ardi Ardani, Tristiadi (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2024)
Social media has a complex impact on suicide rates in early adulthood. On the one hand, social networks provide an important means of establishing social relationships and increasing social support and education. But on the other hand, social media can also cause comparison stress and social pressure, which can increase the risk of depression and suicidal thoughts. Shallow interactions and cyberbullying can also worsen mental health. This research uses a systematic literature review (SLR) method. Through this approach, this research hopes to provide comprehensive, clear and accurate results regarding the impact and consequences of social media use on suicide rates in early adulthood. From the results and discussion it can be concluded that social media has a complex impact on suicide rates in early adulthood. Although social media can provide social support and helpful information, excessive use can also increase the risk of mental disorders and suicidal thoughts. Therefore, cooperation between individuals and governments is needed to minimize the negative impacts of social media and encourage healthy and sustainable use.